THE SOLUTION TO THE PROBLEM OF USING GROUND WATER TO COOL LIVESTOCK BUILDINGS - Thay Ngok Shon; Vo Ti Tin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2017)
Ambient temperature in the central part of Vietnam in summer can reach 32–35°C; in some places it can be more than 42°C. Hot climate strongly affects the animal organism alongside with the animal weight reduction and reduction the quantity of egg-laying in poultry. Therefore, air conditioning in livestock buildings is necessary. There are several ways to cool the temperature in such buildings, and each one has its own advantages and disadvantages. We propose to use underground water at the temperature of 24–25°C for this purpose. One of the methods of cooling sheds for livestock is sprinkler irrigation of water on the roof. For calculating the amount of heat, removed from the indoor air in the shed to the cooling water, in the first approximation specialists believe in some cases that an appropriate amount of heat being removed is determined mainly by heat transfer from the air inside the shed to the cooling water through the surface of the roof, represented by the lower part of the wave that form the surface of a metal tile, neglecting the influence of heat conduction on top of the wave of the tile surface. Consequentially, such a simplification leads to possible errors. Therefore, the authors solved the problem of cooling shed by irrigation of water on the roof by an analytical method. Specifically, we solved the problem of heat conductivity of the fin of the finite length of constant cross section, wherein different sides of the fin are conjugate with different environments. Additionally, the calculation considered the effect of solar radiation. For this purpose, the authors have created a heat balance equation at steady state for any infinitesimal element of the fin, and solved the differential equation afterwards. The authors applied the results for calculating practical problem of ground water irrigation of a roof of a livestock shed made of metal areas tiles.